2021
DOI: 10.3389/fpls.2021.628299
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of the DUF4228 Family in Soybean and Functional Identification of GmDUF4228–70 in Response to Drought and Salt Stresses

Abstract: Domain of unknown function 4228 (DUF4228) proteins are a class of proteins widely found in plants, playing an important role in response to abiotic stresses. However, studies on the DUF4228 family in soybean (Glycine max L.) are sparse. In this study, we identified a total of 81 DUF4228 genes in soybean genome, named systematically based on their chromosome distributions. Results showed that these genes were unevenly distributed on the 20 chromosomes of soybean. The predicted soybean DUF4228 proteins were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 68 publications
3
14
0
Order By: Relevance
“…Proline (Pro), malondialdehyde (MDA), hydrogen peroxide (H 2 O 2 ), and superoxide anion (O 2 – ) levels are important indicators of the effects of abiotic stresses on plant growth ( Leng et al, 2021 ). Proline is a protective agent against osmotic stress; MDA reflects the degree of lipid oxidative damage; H 2 O 2 and O 2 – play immune and signal transduction roles, although excessive accumulation may lead to cell membrane damage ( Du et al, 2018 ; Zhang et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Proline (Pro), malondialdehyde (MDA), hydrogen peroxide (H 2 O 2 ), and superoxide anion (O 2 – ) levels are important indicators of the effects of abiotic stresses on plant growth ( Leng et al, 2021 ). Proline is a protective agent against osmotic stress; MDA reflects the degree of lipid oxidative damage; H 2 O 2 and O 2 – play immune and signal transduction roles, although excessive accumulation may lead to cell membrane damage ( Du et al, 2018 ; Zhang et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…The TIFY protein sequences of Arabidopsis , rice, soybean, apple, and grape were compared using ClustalW in the MEGA-X software. The maximum likelihood (ML) method was used to construct a phylogenetic tree for analyzing the phylogenetic relationship between TIFYs ( Kumar et al, 2016 ; Leng et al, 2021 ). The bootstrap method was used with 1,000 replicates.…”
Section: Methodsmentioning
confidence: 99%
“…Identifying GWAS-based genes controlling salt tolerance in soybean has been a prolonged approach. Previously, many GAWS were conducted to identify the major gene families and their role in salt tolerance in soybean; however, further studies will identify more genes and alleles for a detailed understanding of the genetic mechanism of this trait and strengthen our knowledge to improve breeding programs [ 84 ]. A GWAS was conducted to identify the major gene for soybean salt tolerance.…”
Section: Identifying Gwas-based Genes For Salt Tolerance In Soybeanmentioning
confidence: 99%
“…The expression profile of these genes was characterized by using RNA sequencing data under salt stress. These results showed that DUF4228-70 plays an important role in the response to soybean salt stress [ 84 ]. The CrRLK1L proteins have a key role in salt tolerance in soybean, but their function is not yet fully understood.…”
Section: Identifying Gwas-based Genes For Salt Tolerance In Soybeanmentioning
confidence: 99%